2015
DOI: 10.1080/17441692.2015.1091489
|View full text |Cite
|
Sign up to set email alerts
|

Policing the epidemic: High burden of workplace violence among female sex workers in conflict-affected northern Uganda

Abstract: Sex workers in sub-Saharan Africa experience a high burden of HIV with a paucity of data on violence and links to HIV risk among sex workers, and even less within conflict-affected environments. Data are from a cross-sectional survey of female sex workers in Gulu, northern Uganda (n = 400). Logistic regression was used to determine the specific association between policing and recent physical/sexual violence from clients. A total of 196 (49.0%) sex workers experienced physical/sexual violence by a client. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…This is contrary to prior research, which suggests that GBV is associated with inconsistent condom use among FSWs and their sexual partners (12, 15). Importantly, some of this work has yielded partner-specific results related to violence and condom use (13, 56, 57). Unfortunately, our data lacked specificity regarding perpetrator type (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This is contrary to prior research, which suggests that GBV is associated with inconsistent condom use among FSWs and their sexual partners (12, 15). Importantly, some of this work has yielded partner-specific results related to violence and condom use (13, 56, 57). Unfortunately, our data lacked specificity regarding perpetrator type (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, over two-thirds of participants reported being offered more money to not use a condom with a client. Previous studies have documented sex workers accepting additional financial incentives in exchange for unprotected sex, leading to an increased risk for HIV acquisition (Ballester-Arnal et al, 2014; Ballester, Salmeron, Gil, & Gomez, 2012; Muldoon et al, 2015; Nemoto et al, 2012; Patterson et al, 2012). A study of female sex workers in India conducted by Erausquin et al between 2006 and 2010 identified accepting additional financial incentives for unprotected sex as a risk factor for HIV and STIs (Erausquin, Reed, & Blankenship, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As in other regions in Uganda, ongoing poverty and deprivation have contributed to the presence of an informal economic sex work sector 2 . This is despite the fact that sex work is criminalized in Uganda and sex workers face widespread harassment, discrimination and other human rights violations, including from the police and community members 3 .…”
Section: Introductionmentioning
confidence: 99%